Assessment of stroke knowledge and awareness among primary healthcare providers: A cross-sectional survey from the Kezhou quality improvement in acute stroke care project - Ding, Gui-Bing; Sang, Qiang; Han, Hai-Ji; Wang, Xi-Ming; Wu, Yan-Feng (Frontiers in Public Health, 2023)
Objective Acute stroke care is a highly complex type of emergency medical service (EMS) involving patient-centered care in a highly unpredictable and stressful environment with the help of several busy providers. The ability of primary healthcare providers (PHPs) to identify stroke onset early and further manage referrals to higher-level hospitals becomes critical. Methods We conducted a cross-sectional survey about stroke knowledge and awareness among PHPs in China from September 2021 to December 2021. A total of 289 PHPs were divided into two groups, the stroke treatment window (STW) Aware group vs. the STW Unaware group according to their knowledge on the time window for acute ischemic stroke (AIS) management. Logistic regression analysis was performed to explore the predictors associated with knowledge of the time window for acute stroke management. Results Of 289 PHPs surveyed during the study period, 115 (39.7%) participants were aware of the time window for stroke management and were in the STW Aware group, while 174 (60.2%) were in the STW Unaware group. Forty percent of PHPs in the STW Aware group were familiar with the secondary stroke prevention goal of <140/90 mmHg, compared with 27.01% in the Unaware group (P < 0.05). PHPs were not sufficiently aware of loss of consciousness also a symptom of stroke in two groups (75.7 vs. 62.6%, P < 0.05). A higher proportion of PHPs in the STW Aware group believed that thrombolysis was an effective treatment for AIS (96.5 vs. 79.9%, P < 0.01). Endovascular therapy is indicated for AIS was perceived by a higher proportion of PHPs in the STW Aware group than that in the Unaware group (62.6 vs. 6.9%, P < 0.01). Eighty percent of PHPs in the STW Aware group reported attending training on stroke management compared with 58.1% in the Unaware group (P < 0.01). Logistic regression results showed that the predictors of stroke knowledge and awareness among PHPs included sex (OR: 2.3, 95% CI, 1.2–4.6), received training (OR: 2.9, 95% CI, 1.60–5.1), and times of training per year (OR: 0.70, 95% CI, 0.6–0.9). Conclusions PHPs present with a mild to moderate level of stroke management knowledge in northwest China. Strategies to help increase stroke knowledge and awareness among PHPs should be considered in order to help improve the stroke related health service system.